Hak Waris Perempuan dalam Perspektif Al-Qur’an: Studi Analisis Ayat-ayat Waris dengan Pendekatan Tafsīr Maqāṣidī Waṣfī ‘Āsyūr Abū Zaid - Rihhadatul 'Aisy; Ziyadulhaq; Ade Naelul Huda (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to re-analyze the provisions of women's inheritance rights by applying the framework of Tafsīr Maqāṣidī initiated by Waṣfī 'Āsyūr Abū Zaid, and to examine the relevance of this approach in addressing contemporary issues of justice. This research is a qualitative library-based study. The method employed is descriptive-analytical, applying the framework of Tafsīr Maqāṣidī Waṣfī 'Āsyūr Abū Zaid as the primary analytical tool for examining the inheritance verses (āyāt al-mawārīth) in the Qur'an alongside the interpretations of classical and contemporary exegetes (mufasirūn). The findings reveal that Abū Zaid's maqāṣidī approach views inheritance law not as rigid mathematical rules, but as an instrument to achieve noble objectives (maqāṣid) such as proportional justice (al-'adl al-tanāsubī), where the portion of inheritance is closely related to the burden of financial responsibility. This approach concludes that the spirit of sharī'ah justice can still be realized in the modern context through social ijtihad such as family deliberations (musyāwarah), grants (hibah), and wills (waṣiyyah), which align with the spirit of the Compilation of Islamic Law (KHI) in Indonesia. Thus, Tafsīr Maqāṣidī offers a constructive middle ground between adherence to textual authority and responsiveness to changing times.